Survey on Knowledge and on some Cases of Monkeypox: A Zoonotic Disease Endemic to Ubangian Eco-region of Democratic Republic of the Congo - Koto-te-Nyiwa Ngbolua; Ruphin Djolu Djoza; Jeff Iteku Bekomo; Colette Masengo Ashande; Clarisse Falanga Mawi; Emmanuel Kitete Mulongo; Dorothée Tshilanda Dinangayi; Damien Sha Tshibey Tshibangu; Muhammad Ridwan; Pius T. Mpiana (Britain International of Exact Sciences (BIoEx) Journal, 2022)
The aim of this study was to investigate knowledge on Simian Orthopoxvirosis or Monkeypox in 180 people (129 males and 51 females) using the stratified probability sampling method. The majority of the respondents were (are): 35-50 years old (45.00%), with secondary education (43.33%), farmers (40.56%) and married (80.00%). The disease appears every year, thus demonstrating its endemic nature (98.33% of the respondents); 58.3% of the respondents said that the disease appears very often during the dry season, on the contrary, 40% of the respondents said that the disease appears during the rainy season. However, 1.7% of respondents said that the disease occurs every other season. The majority of respondents (81.1%) said that the cause of the disease is the consumption of bush meat, followed by wild vegetables (3.3%), fish (2.8%), livestock (2.2%) and caterpillars (1.7%) respectively. 65.2% of the respondents use Manihot esculenta to treat the disease locally, and followed by the leaves and wine of Raphia sese (13%), Morinda morindoides (13%) and Myrianthus arboreus (8.7%). Between January 17 and September 10, 2020, 40 cases of monkey pox were admitted to HGR of Businga (Maximum age: 42 years, minimum age: 1 year, average age: 13.3 years). 28 patients were male and 12 female. It is therefore advisable that surveillance be organized in wild animals and bush meat exposed on the market to ensure that they are not contaminated with Monkeypoxvirus. It is thus needed to establish a veterinary laboratory in Nord-Ubangi Province.